2004
DOI: 10.1590/s0100-879x2004000400007
|View full text |Cite
|
Sign up to set email alerts
|

There are more asthmatics in homes with high cockroach infestation

Abstract: Although asthma has been commonly associated with sensitivity to cockroaches, a clear causal relationship between asthma, allergy to cockroaches and exposure levels has not been extensively investigated. The objective of the present study was to determine whether asthma occurs more frequently in children living in homes with high cockroach infestation. The intensity of household infestation was assessed by the number of dead insects after professional pesticide application. Children living in these houses in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…Household exposure to cockroaches and mice has been shown to be associated with higher rates of asthma in inner-city areas both within the United States and in other countries 7,14,29,5153. Exposure to cockroach allergen has also been shown to be associated with persistent childhood wheezing54 and severe asthma 55.…”
Section: Pest Allergens and Asthmamentioning
confidence: 99%
“…Household exposure to cockroaches and mice has been shown to be associated with higher rates of asthma in inner-city areas both within the United States and in other countries 7,14,29,5153. Exposure to cockroach allergen has also been shown to be associated with persistent childhood wheezing54 and severe asthma 55.…”
Section: Pest Allergens and Asthmamentioning
confidence: 99%
“…Since their origin, not only do they present a variety of health hazard when found in our houses, but are also a threat in commercial places, spreading diseases through any food source, that they come in contact with [6]. Cockroaches can cause food poisoning by crawling into food materials [7]. Cockroach bite in humans lead to an extremely infested wound, so cockroach infection should be treated immediately.…”
Section: Introductionmentioning
confidence: 99%
“…A key study by Rosenstreich et al [9] revealed that inner-city children with asthma, who were both sensitized to cockroach and exposed to high levels of cockroach allergen in their homes, presented increased asthma morbidity, with more hospitalizations, more medical visits, and more reported symptoms [9]. These findings were confirmed in subsequent studies carried out in inner-city areas in the United States and in other countries [1215]. Exposure to low levels of Bla g 1 and Bla g 2 has been linked to wheezing among infants in the first 3 months of life and with increased proliferative T cell responses [16].…”
Section: Cockroach Allergy: a Marker For Asthma Severity?mentioning
confidence: 79%